2002
DOI: 10.1007/s001150101176
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss von Persönlichkeitsfaktoren und -struktur auf den Verlauf der Major-Depression

Abstract: The extent to which personality characteristics predict the course of severe depression has been controversially discussed. In a sample of 50 depressed inpatients, the significance of personality characteristics for the prediction of relapse was studied prospectively over 2 years. More than half of the patients studied suffered relapses within this period. Well-known predictors such as the number of previous episodes were confirmed. The personality characteristics studied showed different predictive effects at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This conceptual discrepancy of endogeneity may have led to the present results. Another and more probable reason is that recent studies dealing with TM showed a prevalence of TM between 30 and 70% in endogenous depressive patients [38], and that the TM personality trait can be recognized in neurotic depressive patients almost as frequently as in endogenous depressive patients [39]. In effect, TM is not specific for endogenous depressive patients.…”
Section: Which Dimension Is Important For Distinguishing the Three Sumentioning
confidence: 99%
“…This conceptual discrepancy of endogeneity may have led to the present results. Another and more probable reason is that recent studies dealing with TM showed a prevalence of TM between 30 and 70% in endogenous depressive patients [38], and that the TM personality trait can be recognized in neurotic depressive patients almost as frequently as in endogenous depressive patients [39]. In effect, TM is not specific for endogenous depressive patients.…”
Section: Which Dimension Is Important For Distinguishing the Three Sumentioning
confidence: 99%
“…Regarding the significance of the TMP concept for the long-term outcome of depression, there have only been three studies to date. The results were conflicting: Nakanishi et al [31] found the TMP to predict an unfavorable course, while Marneros et al [33] and Kronmüller et al [34] found the TMP structure rather to be protective.…”
Section: Introductionmentioning
confidence: 72%
“…Der von Tellenbach [16] entwickelte Typus melancholicus beschreibt eine prämorbide Persönlichkeitsstruktur, die durch Gewissenhaftigkeit, Fleiû und Festgelegtheit auf Ordentlichkeit charakterisiert ist. In den meisten Studien zu dieser Fragestellung konnte bei etwa 50 % (30 ± 70 %) der Patienten mit Major Depression eine Typus-melancholicus-Persönlichkeitsstruktur nachgewiesen werden [17]. Die Bedeutung dieser Persönlichkeitsstruktur für den Verlauf affektiver Störungen wird kontrovers diskutiert.…”
Section: Psychologische Aspekteunclassified